Wikipedia and culture of remembrance: The problem of naming war crimes in Yugoslavia - Janjić Stefan (Communication Direction Institute, Novi Sad & University of Belgrade - Faculty of Political Sciences, Belgrade, 2021)
The aim of the research, based on content analysis, is to identify the model of naming articles on war crimes in the former Yugoslavia on the Serbian, Croatian and Bosnian versions of the online encyclopedia Wikipedia, which we observe in this context, following C. Pentzold, as ". global memory place". The sample covers topics that (a) appear on two or three versions of Wikipedia and that (b) are dedicated to war crimes committed during the World War II and the breakup of Yugoslavia. A comparative analysis of the titles of these articles was conducted with the intention of determining the degree of similarity, as well as to consider the potential causes of the difference. The degree of similarity of the titles on war crimes is bigger in the articles concerning the joint struggle of the three nations in the World War II. In contrast, articles dealing with intergroup conflicts during the breakup of former Yugoslavia are characterized by far lower similarity of titles, which are sometimes completely contradictory. The titles of articles on these three versions of Wikipedia do not only serve to indicate a certain term or event, although it is their basic and most common function, but also to emphasize the interpretation of a sensitive topic.